Trends in the adaptability of market dynamics and strategies for the commercialization of bio-based polymers - Sharma, Shagun; Ujjawal, Nishtha; Gupta, Manisha; Yahya, M. Z. A.; Srivastava, Monika; Noor, I.M.; Shyam, Hari Shankar (John Wiley and Sons Inc, 2025)
Bio-based polymers are becoming more popular as more people want to buy goods that are good for the environment and last a long time. However, commercializing these polymers meets several problems, such as high production costs, a limited supply of feedstocks, and a need for more standardization. This paper looks at how the flexibility of market dynamics is changing, how bio-based polymers can be brought to market, the current market trends, the regulatory environment, and the technical advances that have led to the commercialization of bio-based polymers. The paper also lists the critical success factors for the commercialization of bio-based polymers, such as the availability of cost-effective and sustainable feedstocks, the development of efficient production methods, and the creation of reliable supply chains. At the end of the paper, the need for cooperation between industry players, policymakers, and consumers is emphasized to speed up the adoption and commercialization of bio-based polymers.